2005
DOI: 10.3310/hta9390
|View full text |Cite
|
Sign up to set email alerts
|

Is hydrotherapy cost-effective? A randomised controlled trial of combined hydrotherapy programmes compared with physiotherapy land techniques in children with juvenile idiopathic arthritis

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(99 citation statements)
references
References 56 publications
2
80
0
16
Order By: Relevance
“…Six of the studies examined the economic impact associated JIA, while one study considered the impact on total cost of etanercept treatment (93) and another examined the cost-effectiveness of JIA hydrotherapy (94); although these focused primarily on the cost-effectiveness or effect on treatment cost of specific therapies, they are included here because they provide a comparison for standard therapies.…”
Section: Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…Six of the studies examined the economic impact associated JIA, while one study considered the impact on total cost of etanercept treatment (93) and another examined the cost-effectiveness of JIA hydrotherapy (94); although these focused primarily on the cost-effectiveness or effect on treatment cost of specific therapies, they are included here because they provide a comparison for standard therapies.…”
Section: Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…Several studies have shown that children with polyarticular JIA are less active than their healthy counterparts and exhibit reduced aerobic and anaerobic exercise capacity (66,67). There is evidence that regular physical conditioning improves joint pain and range of motion in patients with JIA (68,69). A number of reports have suggested that engagement in both low-and high-intensity exercise programs results in improved physical function and decreased pain in patients with JIA (70,71), although a Cochrane meta-analysis of existing randomized controlled trials did not show statistically significant benefits (72).…”
Section: Physical Therapy and Sleep Interventionsmentioning
confidence: 99%
“…Abban a vizsgálatban, ahol 78 juvenilis krónikus arthritisben szenvedő beteg szárazföldön és a vízben (hidroterápia) végzett kezeléssorozatát hasonlították össze, azonos életminőség-nyereséget eredményezett mind a két kezelési mód (eredményességre vetített azonos költség) [1]. Egy másik vizsgálatban, ahol arthrosisban szenvedők hidroterápiáját vizsgálták, a hidroterápia hatékonysága a vizsgált klinikai paraméterekben jobb volt, és a betegek is nagyobb életminőség-javulást jeleztek, mint a szárazföldön végzett gyakorlatok esetében.…”
Section: Költséghatékonysági Vizsgálatokunclassified